Evaluate the Effect of Dendrosomal Curcumin on Expression Level of HOTAIR Long Noncoding RNA in MCF-7 Breast Cancer Cell Line - Maryam Mehrabi; Sara Alemohammad; Reza Dashtebozorgi; Maryam Tahmasebi Birgani; Mohammad Reza Hajjari; Javad Mohammadi-Asl (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2023)
Introduction: Breast cancer is one of the most common malignancies in women. Treatment with herbal drugs has been considered by researchers due to the lower side effects. Curcumin is a polyphenol extracted from turmeric with confirmed anti-cancer properties. Curcumin is water-insoluble with rapid metabolism. Drug delivery using nano-carriers is suggested to overcome such limitations. The aim of this study was based on evaluating the effect of Dendrosomes curcumin on expression level of HOTAIR long noncoding RNA in MCF-7 breast cancer cell line. Methods: This study was an applied basic research. Firstly, curcumin was loaded in dendrosomes and the entry of dendrosomal curcumin into cells was studied using fluorescent microscopy.  Cell death was investigated using MTT assay and apoptosis detection kit. The expression of HOTAIR gene was measured using real-time PCR. Increased expression of this gene was reported in a wide range of tumors. The data were analyzed using GraphPad Prism V9.5 statistical software, using NOVA one-way statistical analysis and Student t-test; the results were reported as mean ± standard deviation. Results: Dendrosomes increased the solubility of curcumin. The effective inhibitory doses of dendrosomal curcumin after 24 and 48h treatment were 25 and 20 micromolar, respectively. The percent of cells undergoing early apoptosis were 22.97±0.03 and 56.22±0.05, respectively, which was statistically significant in comparison with non-treated control cells. Following 24 and 48h treatment with 20 micromolar of dendrosomal curcumin, the HOTAIR gene expression was significantly decreased (P=0.001). Conclusion: These findings suggest that dendrosomal curcumin may promote breast tumor cells toward programmed cell death by reducing HOTAIR gene expression.